(untitled) (Itinera, 2015)
In this article, the Author analyses the Bradleian concept of contradiction and the thesis herewith proposed consists in thinking that the so-called «Russell’s antinomy», one of the most popular and most discussed theoretical points in the modern and contemporary philosophy, is rooted or better is implied in Bradley’s system. The Author argues that, formulating and presenting it at Frege, Russell articulated a question opening a consequent philosophic perspective already conceptually implied by Bradley’s theory of relations.